PENGARUH INTRANET TERHADAP PENINGKATKAN KINERJA KARYAWAN PADA PT. PERTAMINA REFINERY UNIT II DUMAI - Bima, Gusti Agung Putra; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Development technology and information has been widely used by companies to improve employee performance. One such company is PT. Pertamina Refinery Unit II Dumai. The company uses an intranet media. Information technology such as the Internet, creates economic value by acting as leverage and the utilization of human resources and other physical resources owned by the company. Companies that have the resources and capabilities of information technology in the form of intranet has a positive relationship with the employee's performance.In theory Resources Based Theory states the relationship between information technology and corporate performance. The purpose of this study is to determine how much influence the use of intranet in improving the performance of employees at PT. Pertamina Refinery Unit II Dumai.The method used in this research is quantitative method with the kind of explanation survey. Data collection techniques in this study using a questionnaire. The location of this research is PT. Pertamina Refinery Unit II Dumai. Total population of 50 people, and the whole used as respondents. Sampling using census techniques. To find out how much influence these two variables, the researchers used a simple linear regression analysis. Questionnaires for data processing, is done by using the program Statistical Product And Service Solution (SPSS) Windows version 20.Results of research on the use of intranet in improving the performance of employees of PT. Pertamina Refinery Unit II Dumai, regression coefficient values obtained in this study is Y = 10.260 + 1.264 X with a significance level of 0.00. significance value 0.00 smaller than the value of 0.05. This indicates that the H0 is rejected and Ha accepted. It mean the use of intranet consisting of indicators of e-information, e-communication and e-transaction has an influence on improving the performance of employees at PT. Pertamina Refinery Unit II Dumai measured by indicators of quality, quantity, timeliness, efficiency and independence.Keywords : Intranet, Employees Performances